The Processing Propagation of Microalgae Botryococcus Sp. Cultivation in Palm Oil Mill Effluent Materials - L. Abdullah; N.M. Apandi; N.M. Sunar; S.N.H. Arifin; M. Haron; R. Nagarajah; K. Cheong; C. Heng; C.F. Soon; M. Nabiałek (Archives of Metallurgy and Materials)
Palm Oil Mill Effluent Materials (POME) are significantly more contaminated than municipal sewage due to their high chemical and biological oxygen demand (BOD and COD). This study examines the properties of POME wastewater under typical physical settings to track the growth conditions of microalgae, namely Botryococcus sp., in various volumes at varying POME dilutions. Begin with analyzing POME’s water quality measurements and conclude the growing conditions of microalgae. Botryococcus sp. microalgae could not flourish in diluted raw POME. However, it was well propagated in diluted anaerobic POME under adequate light and oxygen conditions. The finding shows that diluted anaerobic POME 70% is the ideal dilution for microalgae Botryococcus sp. to proliferate. Raw POME is physically described as a thick, brownish liquid with a high total solids and turbidity concentration that is contained in water. The study explores the use of Botryococcus sp. culture and propagation in POME materials for sustainable bioenergy production, highlighting the potential of microalgae for future economic benefits.